Development and Validation of a Novel Diagnostic Test for Human Brucellosis Using a Glyco-engineered Antigen Coupled to Magnetic Beads. - Ciocchini, Andres Eduardo (2013)
Brucellosis is a highly contagious zoonosis and still a major human health problem in endemic areas of the world. Although several diagnostic tools are available, most of them are difficult to implement especially in developing countries where complex health facilities are limited. Taking advantage of the identical structure and composition of the Brucella spp. and Yersinia enterocolitica O:9 O-polysaccharide, we explored the application of a recombinant Y. enterocolitica O:9-polysaccharide-protein conjugate (OAg-AcrA) as a novel antigen for diagnosis of human brucellosis. We have developed and validated an indirect immunoassay using OAg-AcrA coupled to magnetic beads. OAg-AcrA was produced and purified with high yields in Y. enterocolitica O:9 cells co-expressing the oligosaccharyltransferase PglB and the protein acceptor AcrA of Campylobacter jejuni without the need for culturing Brucella. Expression of PglB and AcrA in Y. enterocolitica resulted in the transfer of the host O-polysaccharide from its lipid carrier to AcrA. To validate the assay and determine the cutoff values a receiver-operating characteristic analysis was performed using a panel of characterized serum samples obtained from healthy individuals and patients of different clinical groups. Our results indicate that, using this assay, it is possible to detect infection caused by the three main human brucellosis agents (B. abortus, B. melitensis and B. suis) and select different cutoff points to adjust sensitivity and specificity levels as needed. A cutoff value of 13.20% gave a sensitivity of 100% and a specificity of 98.57%, and a cutoff value of 16.15% resulted in a test sensitivity and specificity of 93.48% and 100%, respectively. The high diagnostic accuracy, low cost, reduced assay time and simplicity of this new glycoconjugate-magnetic beads assay makes it an attractive diagnostic tool for using not only in clinics and brucellosis reference laboratories but also in locations with limited laboratory infrastructure and/or minimally trained community health workers.